Waste Management Program of Kotamobagu City Environment Office - Warouw, Salomon Fernando; Dilapanga, Abdul Rahman; Tarore, Steven (Technium Social Sciences Journal, 2025)
The purpose of this study was to determine the performance of the Waste Management Program at the Kotamobagu City Environmental Service in terms of reporting the implementation of its activity program. The approach used in this research is a qualitative descriptive approach. with the focus of research on the Performance of the Waste Management Program at the Kotamobagu City Environmental Service, with sub-focus: Program implementation, Human resources, Commitment and Compliance, Organizational culture. This research examines the performance of the Waste Management Program in Kotamobagu City, on program implementation, human resources, commitment and compliance, and organizational culture. Weaknesses in structural coordination and internal communication negatively impact monthly reporting. Good leadership can improve the distribution of work and increase efficiency. Unclear Standard Operational Procedures (SOPs) and undocumented reporting reduce transparency and accountability. SOP updates and accountability training are urgently needed. Leadership influences work culture, and performance evaluation is necessary for improvement. To optimize performance, improved internal coordination and communication, equitable redistribution of tasks, effective leadership, SOP updates, and the establishment of a strong evaluation culture are needed. Regular and documented reporting will improve transparency, accountability and efficiency, supporting good governance principles.